Development of Microtik Router Bandwidth Management Applicatio at PLN Office Muara Labuh - Januardi, Cecep; Komala Sari, Putri (Jurnal Sains Informatika Terapan, 2023)
Bandwidth instability is a serious problem where the need for using the internet is in the process, it is necessary to manage bandwidth so that bandwidth is properly organized but changes that will be made to bandwidth management require experts in Mikrotik routers, so an application is needed to manage this bandwidth and can be used by ordinary people so that errors in configuration will be avoided because the configuration is done automatically as desired and can certainly help bandwidth management at a lower cost. Making this application by using data collection methods by taking data at PLN Muara Labuh area, interviewing field supervisors, studying literature that supports problem solving and Unified Modeling Language (UML) for software designers along with software testing. The application is built using django.